Investigating traffic light violations by cyclists in Dublin City Centre - CAULFIELD, BRIAN (My University, 2015)
This research examines the behavior of cyclists in Dublin City with specific regard to red light running. A number of specific research questions are raised by this study. These quest ions address the impact of different infrastructure types on red light running, as well as the behavioral patterns and demographics of offending cyclists. Two data collection methods were used to gather information on cyclists in Dublin City - an observa tional survey and an online questionnaire. The observational surveys examined cyclist compliance with different traffic signal systems and the impact of on - road and off - road cycle infrastructure. An online questionnaire was used to get direct feedback from cyclists in Dublin City on the reasons (if any) they decide to commit infringement at traffic lights. With the recent growth of cycling in Dublin City (as well as many other international cities) it is vital to accommodate and manage this growing demand by ensuring the safety and road discipline of cyclists. The next few years will be crucial for the continued development of cycling in Dublin, particularly due to the increasing investment by transport planners in cycle infrastructure. It is therefore imp ortant to identify now the main factors which influence cyclist's decisions to break red lights in order to guide local traffic authorities in their efforts to reduce such transgressions
PUBLISHED
Keywords: Cyclists; Dublin; Smart & Sustainable Planet